Ocena ekonomicznej efektywności inwestycji w odnawialne źródła energii na przykładzie ciepłowni biomasowej w Reczu - Baron, Magdalena (Economic Effectiveness of Renewable Energy Projects Assessment, the Case of Biomass Heat-generating Plant in Recz, 2007)
The study concerns methodical aspects of economic effectiveness of renewable energy projects assessment, based on cost-benefit analysis CBA. The author presents differences between financial and economic effectiveness of investment projects and provides the theory of distortions - market and policy failures, as a reason of these differences. The paper is a detailed presentation of the concept of technological external effects, as a main distortion in respect to renewable energy projects. It discusses the corrections allowing the transfer from financial to economic calculation and the case of biomass heat-generating plant in Recz.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 54-65